Problems with Complete Systematic Land Registration Regulations Perspective of Legal Certainty - Cucu Sudrajat; Toto Tohir Suriaatmadja; Lina Jamilah (Borong Newinera Publisher, 2023)
One of the government's endeavors to promote legal clarity and maintain communal land rights is to register all land in Indonesia. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency is in charge of a statewide program called Complete Systematic Land Registration, which aims to speed up the land registration process. In accordance with the directive issued by the Minister of Agriculture and Spatial Planning/National Land Agency Director. A number of problems prevent the implementation of Complete Systematic Land Registration, including inconsistencies in government regulations, the Minister of Agrarian Affairs and Spatial Planning's regulations, and the Law on Regional Taxes and Regional Retributions. Legitimacy Theory, Legal Validity Theory, and Legal Certainty Theory all stipulate that statutory regulations may not conflict with other regulations in order to provide certainty; these theories should be followed if the government is serious about achieving the goal of Complete Systematic Land Registration. Legislation provides safeguards for those with title to land, free of normative conflicts and the potential for multiple interpretations at the administrative and judicial levels. Both the normative legal approach and the synchronization legal approach will be included into the analysis of the qualitative data used in this study.